Efforts to Improve Understanding of Learning Outcomes of Allah's Obligatory Attributes in Students at MTS Ibnu Ajhari Tambelang - Yanti; Aryatie, Yayah; Rosnawati, Yanti (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
Students' understanding of the obligatory attributes of Allah in learning aqidah is an important aspect of Islamic education, especially at the Madrasah Tsanawiyah (MTs) level. The obligatory attributes of Allah are part of the basic study of aqidah and serve as a guideline in understanding the attributes of Allah SWT. However, in practice, many students have difficulty understanding this concept in depth. This difficulty can be caused by less interactive learning methods and lack of student involvement in the learning process. This study aims to improve the understanding of grade VII MTs students of the obligatory attributes of Allah through the application of innovative and effective learning methods. The research method used is classroom action research (CAR) with qualitative and quantitative. Data collection techniques are carried out through observation, interviews, evaluation tests, and student questionnaires. The results of the study show that the application of interactive learning strategies, such as group discussions, the use of audiovisual media, and contextual approaches, can significantly improve students' understanding. This can be seen from the results of learning evaluations that are better than before and the positive responses from students to the learning methods applied. In addition, this learning strategy also increases students' motivation and active participation in the learning process, so that they can easily understand and remember the obligatory attributes of Allah. Thus, this study confirms that innovative learning methods have a positive impact on students' understanding and involvement in the process of learning the creed.